Effectiveness of Polish labour market: Taxonometric analysis of European Union countries in the years 2004-2007 - Balcerzak, Adam P.; Rogalska, Elżbieta (Publishing House of the Wrocław University of Economics, 2009)
The main aim of this paper was to verify the changes of effectiveness of Polish labour market in the international perspective. Poland was classified in the last place of the ranking in the years 2004-2006 and was the last but one in 2007. The analysis of individual diagnostic variables, which were finally used as a base for synthetic variable, shows that in spite of improvement in case of unemployment rate Poland was not able to implement reforms discouraging employees from early retirement. This results in very low level employment in Poland, which is the main reason for distant positions of the country in the ranking. This means that Polish government’s main priority should be creation of incentives and institutional rules that would result in increasing the rate of employment. A success in this field is a condition of improving relatively low effectiveness of Polish labour market. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 40-48